Rapid neurodevelopmental assessment of newborn: a promise to ensure proper growth and development of all newborns in Bangladesh - Salwa, Zeena; Shilpi, Asma Begum; Begum, Lutfun Nahar (International Journal of Contemporary Pediatrics, 2024)
Background: Neonates are susceptible to neurodevelopmental impairments due to various factors. The aim of the study was to use the n-RNDA tool to identify such impairments in neonates, enabling early interventions for improved outcomes. Methods: This facility-based cross-sectional study was conducted in Square Hospital Child Development Center from April 2019 to Nov 2021 with all neonates between ages of 15-28 days. A total 2928 neonates were enrolled and underwent n-RNDA assessment for detection of any types of neurodevelopmental impairments. Results: Among 2928 enrolled neonates, 8.1% exhibited neurodevelopmental impairments. Majority (60.6%) were from the NICU. Impairments varied across domains, with gross motor skills (99.2%) being most prevalent. Causes included respiratory distress syndrome (74%), sepsis (60%), and others. The study population was primarily urban (99.1%), with 100% parental literacy. Conclusions: The n-RNDA screening program for neonates facilitates early assessment, interventions, and long-term follow-up, potentially enhancing outcomes and quality of life. These findings advocate for policy development to institutionalize n-RNDA for early diagnoses and better outcomes in all neonates.